Shoulder muscle imbalance as a risk factor for shoulder injury in elite badminton players: A prospective study - Guermont, H.; Mittelheisser, G.; Reboursière, E.; Gauthier, A.; Drigny, J. (Physical Therapy in Sport, 2023)
Objectives To assess the impact of preseason shoulder testing on the risk of significant shoulder injury (SSI) in elite badminton players.